Characterization of melanoidins derived from Brewers’ spent grain: New insights into their structure and antioxidant activity - Patrignani, Mariela (2020)
Melanoidins, formed at the final stages of Maillard reaction (MR) present important physiological activities, but their structure and reaction pathways are largely unknown in real food systems. In the present work, these bioactive compounds derived from Brewers’ spent grain (BSG) with different roasting degrees were analyzed. Results showed that BSG could be considered a more important source of bioavailable antioxidants than what it was reported in previous studies. During MR development, proteinic structures are partially lost while a carbohydrate skeleton is formed. The crystallinity is reduced and the structure sets into a conformation with a peak centred at 20°(2θ), stable with the increasing thermal treatment. While MR continues the development of browning compounds increases, the antioxidant activity rises and phenolic compounds are bind to the melanoidin structure (P ≤ 0.05). Moreover, FTIR analysis showed a dominance of α‐glyosidic linkage and the presence of furanose rings in the melanoidins structure.